Endoplasmic reticulum stress-related genes as prognostic and immunogenic biomarkers in prostate cancer - Lilin Wan; Yunxia Fan; Tiange Wu; Yifan Liu; Ruixin Zhang; Saisai Chen; Chenggui Zhao; Yifeng Xue (European Journal of Medical Research, 2024)
Abstract Background The metastasis and aggressive nature of prostate cancer (PCa) has become a major malignancy related threat that concerns men’s health. The efficacy of immune monotherapy against PCa is questionable due to its lymphocyte-suppressive nature. Method Endoplasmic reticulum stress- (ERS-) and PCa-prognosis-related genes were obtained from the Molecular Signatures Database and the Cancer Genome Atlas database. The expression, prognosis and immune infiltration values of key genes were explored by “survival R package”, “rms”, “xCELL algorithm”, and univariate–multivariate Cox and LASSO regression analyses. The “consensus cluster plus R package” was used for cluster analysis. Result As ERS-related genes, ERLIN2 and CDK5RAP3 showed significant expressional, prognostic and clinic-pathologic values. They were defined as the key genes significantly correlated with immune infiltration and response. The nomogram was constructed with T-stage and primary treatment outcome, and the risk-prognostic model was constructed in the following way: Riskscore = (− 0.1918) * ERLIN2 + (0.5254) * CDK5RAP3. Subsequently, prognostic subgroups based on key genes classified the high-risk group as a pro-cancer subgroup that had lower mutation rates of critical genes (SPOP and MUC16), multiple low-expression immune-relevant molecules, and differences in macrophages (M1 and M2) expressions. Finally, ERLIN2 as an anti-oncogene and CDK5RAP3 as a pro-oncogene were further confirmed by cell phenotype assays and immunohistochemistry. Conclusion We identified ERLIN2 and CDK5RAP3 as ERS-related genes with important prognostic and immunologic values, and classified patients between high- and low-risk subgroups, which provided new prognostic markers, immunotherapeutic targets, and basis for prognostic assessments.